2018
DOI: 10.1016/j.exger.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Lower protein and higher carbohydrate intake are related with altering metabolic syndrome components in elderly women: A cross-sectional study

Abstract: Either high carbohydrate or low protein intake would be risk factors for altering MetS components and the presence of MetS in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 48 publications
3
13
3
Order By: Relevance
“…Our results demonstrated that older individuals with LPI presented higher body mass, BMI, and fat mass. This result is consistent with other studies (Gregorio et al, 2014;Isanejad et al, 2016) and could demonstrate a compensation of protein consumption for carbohydrates, which may lead to the development of obesity and its comorbidities (Nabuco et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results demonstrated that older individuals with LPI presented higher body mass, BMI, and fat mass. This result is consistent with other studies (Gregorio et al, 2014;Isanejad et al, 2016) and could demonstrate a compensation of protein consumption for carbohydrates, which may lead to the development of obesity and its comorbidities (Nabuco et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Some researchers have suggested that the amount of protein intake for older people should be at least 1.2 g/kg/day (Bauer et al, 2013), opposing the current RDA. Moreover, cross-sectional studies indicated an influence of protein intake on health status (Gregorio et al, 2014; Isanejad et al, 2016; Nabuco et al, 2018), such as improvement in physical performance, muscular strength, and abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%
“…The only exceptions are the carbohydrates next to the proteins, which were statistically significantly correlated with total serum proteins, unlike Praveen S et al [ 46 ]. Therefore, a higher carbohydrate intake was related to lower protein consumption and lower body weight, similar to Bopp MJ et al [ 47 ], unlike Nabuco HCG [ 48 ], which obtained a drop in serum proteins based on high carbohydrate but normal protein intake. These comparisons can also be described by the glycogenosis process, where the protein turnover is altered.…”
Section: Discussionsupporting
confidence: 73%
“…According to a review study investigating the effect of carbohydrate consumption on metabolic parameters in diabetic patients, high intake of carbohydrate was associated with higher serum triglyceride levels and lower HDL levels [24]. Similar results were reported in a cross-sectional study of older women [25]. While abdominal obesity assessed by BMI and WC was negatively associated with HDL levels, it was positively associated with triglyceride levels [22, 26].…”
Section: Discussionmentioning
confidence: 61%